KEBIJAKAN HUKUM PIDANA TERHADAP ANAK HASIL DARI TINDAK PIDANA PEMERKOSAAN - Anggun Krisnawati; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The criminal act of rape is an attempt to wreak sexual desire by a man against a woman by means of being considered violating according to morals and laws. And the most detrimental impact of rape victims is the unwanted pregnancy. And, rape can even destroy two generations, namely victims of rape and their innocent children, because their legal status is an illegitimate child and an illegitimate mother. This is what the state must pay attention to, especially in providing a form of protection for children who are the result of rape who are innocent, so that the child who is the result of rape feels justice for the harm he has suffered.This type of research is normative legal research, where normative legal research is carried out by researching, namely examining the application of the rules or norms in positive law regarding the principles of law of justice, this research uses the nature of juridical research, because the author intends to provide a clear picture. clear and detailed regarding fair protection of children resulting from the crime of rape.From the research results, it is concluded that the criminal law policy against children resulting from the crime of rape must be carried out optimally in order to achieve the best results of criminal legislation in the sense that it fulfills the requirements of justice for children from the results of the crime of rape, in order to achieve justice in the present and in the future they will be given protection such as health, education, economic, social and psychological problems. As well as ensuring the welfare of children from the results of the crime of rape, which currently has no special treatment for children from the results of the crime of rape, because the act is based on coercion and threats from the perpetrator of rape.Keywords: Policy – Criminal Law – Children – Results – Rape